Monitoring Distribution Dynamics of EV RNA Cargo Within Recipient Monocytes and Macrophages - Alfandari, Daniel; Ben Ami Pilo, Hila; Abou Karam, Paula; Dagan, Osnat; Joubran, Carine; Rotkopf, Ron; Regev-Rudzki, Neta; Porat, Ziv (Frontiers in Cellular and Infection Microbiology, 2022)
Extracellular vesicles (EVs) are produced across almost all the living kingdoms and play crucial roles in cell-cell communication processes. EVs are especially important for pathogens, such as the Plasmodium falciparum (Pf) parasite, the primary species to cause human malaria. Pf is able to modulate its host’s immune response from a distance via the EV delivery of diverse factors, such as proteins and nucleic acids. We previously showed that imaging flow cytometry (IFC) can be effectively used to monitor the uptake of various cargo components of malaria-derived EVs by host human monocytes. Here, we advance this approach one step further by demonstrating the ability to directly monitor and compare the temporal dynamics of the cargo distribution pattern within two different recipient immune cells, monocytes and macrophages. By staining the EVs’ RNA cargo and monitoring the signal, we were able to evaluate the kinetics of its delivery and measure different parameters of cargo distribution post internalization. Interestingly, we found that while the level of EV uptake is similar, the distribution pattern of the RNA cargo signal differs significantly between these two types of recipient immune cells. Our results demonstrate that this method can be applied to study the post-uptake distribution dynamics and fate of EV cargo within different cell types.